PERANAN PENDAMPING DAN PARTISIPASI PETANI DALAM PROGRAM UPSUS TANAMAN PADI SAWAH DI KECAMATAN GADINGREJO KABUPATEN PRINGSEWU - Prasetya, Dhanar Yoga; Effendi, Irwan; Nurmayasari, Indah (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2019)
This study aims to know the roles of Extension Workers and co-workers, and farmers’ participation in the Upsus rice plant program in Gadingrejo, Pringsewu District. Data collection was conducted in August 2017 and involved 54 farmer respondents. The research method used is a survey method. The analytical method used is qualitative descriptive analysis and uses Rank Spearman correlation. The results showed that the average percentage of the role of Extension Workers is 74.14 percent, Babinsa is 71.98 percent, and students/alumni is 72.28 percent. The average percentage of farmers’ participation in the program is 72.79 percent. The level of rice production and farmers’ income in the Upsus program averaged 4,727 kg/ha/season with an average income of Rp. 8,148,403.00 /ha/season. The roles of Extension Workers and students/alumni in the Upsus program are significantly related to the participation of farmers, while the role of Babinsa is not significantly related to the participation of farmers in the program. Farmers’ participation in the Upsus program is significantly related to farm production.Key words: farmers’ participation, the role, Upsus program